Empatía y alteridad en Mariátegui: una lectura de los 7 ensayos (2013)
This paper examines the concepts of otherness present in the José Carlos Mariátegui´s Seven Interpretative Essays on Peruvian Reality. This work shows there is a complex representation of otherness, which distinguishes among others (the other of the colonial, Chinese, Black, and Indian heritage) and different ways to relate to them. Mariátegui proposes a break in how otherness is represented in Latin America in the first half of the twentieth century through a gesture of empathy trying to put herself in the indigenous shoes to make a diagnosis of the Peruvian reality and build a project that rescues the native to project it into the future.